Sedimentary Hg isotope signatures overprinted by lateral transport and upwelling-driven Hg recycling in the Benguela upwelling system - Yaqiu Zhao; Michelle L. Abshire; Stephen J. Romaniello; Jiayu Wu; Ruoyu Sun; Yi Liu; Jiubin Chen; Wang Zheng (Geochimica et Cosmochimica Acta, 2026)

Brown skua Catharacta antarctica breeding distribution and population trends on sub-Antarctic Marion Island, 1987–2023: implications of alien invasive species - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Eleanor A. Weideman; Lucy K. Smyth; Mia Cerfonteyn; Stephen Hunter; Peter G. Ryan (Polar Biology, 2026)
Predator-prey relationships on islands are often profoundly altered by invasive species. Brown skuas Catharacta antarctica are predator-scavengers at sub-Antarctic islands, where their population dynamics are linked to food availability. On Marion Island, skua population size and breeding distribution appear to have shifted in response to changes in burrowing petrel populations, which were severely impacted by feral cat Felis catus predation before cats were eradicated in 1991. We compare estimates of brown skua population size, breeding distribution, and fledgling production on Marion Island from studies conducted between 2010 and 2023 to earlier studies before cats were eradicated, including an extensive survey in 1987–1988. With increased search effort in 2023, we recorded 983 breeding territories, exceeding the 1987–1988 estimate of 878 territories, despite a slight decrease in average production, from 1.26 fledglings per pair per year in 1987–1988 to 1.10 between 2010 and 2022 ( n = 3 surveys). Most notably, there has been a shift in the distribution of breeding sites: territories in coastal areas where skuas mainly prey on penguins have increased by 39% since 1987–1988, whereas they decreased by 31% at inland sites where petrels are the main prey. This coastward shift is surprising given the modest recovery in petrel numbers since cats were eradicated and recent decreases in penguin populations. These counterintuitive findings establish a baseline for monitoring ecological change on Marion Island. As we expect more impacts associated with climate change, highly pathogenic avian influenza and invasive species management, regular surveys of predators such as brown skuas become increasingly valuable.

MATHFI: A Multi-scale Adaptive Thresholding and Hierarchical Feature Integration Network for Retinal Vessel Segmentation and Quantitative Biomarker Analysis - Michelle N. Tolentino; Stephen Lloyd C. Abenoja; Jonathan C. Morano; Dan Michael A. Cortez; Ymir M. Garcia; Kuo-Sheng Cheng (Journal of Medical and Biological Engineering, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dynamics of Respired Dissolved Organic Carbon in a Stream - Robert O. Hall; Erin R. Hotchkiss; Michelle A. Baker; Stephen Plont (Ecosystems, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Evolution of the Resin Daisies: Biogeography of the Genus Pteronia L. (Astereae, Asteraceae) in the Arid and Semi‐Arid Habitats of Southern Africa - Anifat Olayemi Bello; James Stephen Boatwright; Anthony Richard Magee; Nicola Bergh; Michelle van der Bank (Journal of Biogeography, 2026)
Aim The species‐rich flora of southern Africa results from Neogene species accumulation involving multiple geographically distinct radiations. This diversity was enhanced by lineage cross‐seeding amongst several broadly defined regional floras. We examine the relative ages and the role of shifts between southern African habitats in the Desert and Fynbos floras in a single lineage of Cape daisies, the resin daisy genus Pteronia . Using these xeric‐adapted shrublets, we more finely dissect the radiations to explore the relative ages of occupation and diversification in the different winter‐rainfall floras of South Africa (fynbos, renosterveld, and succulent karoo vegetation), as well as the adjacent arid and semi‐arid Desert, Nama Karoo and Kalahari Savanna floras. Location Southern Africa, focusing on the winter‐rainfall floras and adjacent arid/semi‐arid regions in the south‐western corner of the subcontinent. Methods A dated species‐level molecular phylogenetic hypothesis for Pteronia and outgroups is presented. Eight floristic and biogeographic areas of distribution are identified. Ancestral areas and the timing, frequency, and direction of range change events amongst these areas are inferred using the statistical DEC model on a sample of dated posterior trees. Results Pteronia is strongly supported as monophyletic and began diversifying in the late Miocene, consistent with other Cape radiations, particularly those associated with arid regions. From the ancestral range of the genus in the northern parts of the Succulent Karoo and/or fynbos vegetation, the first novel vegetation type to be colonised was Nama Karoo at the end of the Miocene, followed by south‐eastern Succulent Karoo, renosterveld in the early Pliocene, and Kalahari Savanna in the Late Pliocene. The subtropical thicket and Bushmanland bioregions were colonised more recently in the Pleistocene. Early diversification in Pteronia gave rise to two lineages. The first lineage diversified in and remains strongly confined to the northern Succulent Karoo. The second lineage diversified in both fynbos and a range of adjacent arid/semi‐arid vegetation types, experiencing more frequent shifts between habitat types. Main Conclusions Speciation in Pteronia is associated with two geographic patterns: firstly, diversification within single habitat types, which applies to the northern succulent karoo and to a lesser extent, the fynbos vegetation, and secondly, diversification associated with shifts between habitat types. Habitat shifts appear to be strongly influenced by habitat adjacency and ecological similarity. Understanding the nature and timing of historical habitat shifts in Pteronia may contribute to the knowledge of interactions between different floras within South Africa, both winter and summer rainfall, as well as the timing of colonisation of these areas, particularly the Succulent and Nama Karoo.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Bovine milk glycoproteins concentration influences bacterial growth and anti-pathogenic bioactivities relevant to the infant gut in vitro - Iwona Dziembała-Gładysz; Marie Le Berre; Stephen Cunningham; Laura Walsh; Uthesh Umapathy; Yousef Joubran; Gerard T.A. Fleming; David A. Goulding; Lokesh Joshi; Jonathan O'Regan; Michelle Kilcoyne (International Dairy Journal, 2026)

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Extreme Weather Magnifies the Effects of Forest Structure on Wildfire, Driving Increased Severity in Industrial Forests - Jacob I. Levine; Brandon M. Collins; Michelle Coppoletta; Scott L. Stephens (Global Change Biology, 2025)
Despite widespread concern over increases in wildfire severity, the mechanisms underlying this trend remain unclear, hampering our ability to mitigate the severity of future fires. There is substantial uncertainty regarding the relative roles of extreme weather conditions, which are exacerbated by climate change, and forest management, in particular differences between private industrial timber companies and public land agencies. To investigate the effects of extreme weather and forest management on fire severity, we used light detection and ranging (LiDAR) data to characterize pre‐fire forest structure across five large wildfires which burned 460,000 ha in the northern Sierra Nevada, California, USA. We found that the odds of high severity fire occurrence in these fires were 1.45 times higher on private industrial land than in publicly owned forests, an effect equivalent to a three standard deviation decrease in fuel moisture. Next, we quantified the relationships between key forest structure metrics and the probability of high severity fire, as well as how these relationships were modified by extreme weather. We found that dense, spatially homogeneous forests with high ladder fuels were more likely to burn at high severity. Extreme weather magnified the effect of density, suggesting that treatments which remove overstory trees are especially important in extreme conditions. Forests managed by private industry were more likely to be dense, spatially homogeneous, and contain high ladder fuel loads than publicly owned forests, offering a potential explanation for the increase in high‐severity fire occurrence on private industrial land. Overall, these results illustrate the need for comprehensive forest management to mitigate fire severity in a warmer future.

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

Noradrenergic modulation of play in Sprague-Dawley and F344 rats - Stephen M. Siviy; Michelle A. Martin; Celeste M. Campbell (Psychopharmacology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Assessment of laser ablation and solution-based ICP-MS applications commonly used in otolith geochemical analysis of marine teleosts - Michelle Zapp Sluis; Daniel L. Lippi; Phillip J. Sanchez; Nathaniel R. Miller; Shane A. Stephens; Beatrice P. Ferreira; Jay R. Rooker (Frontiers in Marine Science, 2025)
Different applications of inductively coupled plasma mass spectrometry (ICP-MS) have the potential to influence results of otolith geochemical assays. Laser ablation and solution-based ICP-MS were compared on paired otoliths from three species of juvenile fish representative of estuarine (red drum [ Sciaenops ocellatus ]), coastal/reef (gray parrotfish [ Sparisoma axillare ]), and pelagic (blackfin tuna [ Thunnus atlanticus ]) ecosystems. Additionally, two laser ablation techniques (continuous line transects and series of spots) were performed to determine whether these two commonly used approaches yielded comparable results. No significant differences existed between line transects and spots for any of the three species investigated, with high correlations occurring for all otolith element:Ca (E:Ca) values retained for statistical testing (Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca), suggesting that both laser ablation techniques produced equivalent otolith E:Ca values. In contrast, pronounced differences in E:Ca values were detected between laser ablation (across otolith transverse section) and solution-based (whole otolith dilution) applications on paired sagittal otoliths. While some E:Ca discrepancies varied among the three species, overall otolith E:Ca values were higher when quantified by laser ablation, except for Ba:Ca which tended to be higher when analyzed by solution-based ICP-MS. Differences observed between laser ablation and solution-based applications are the result of the allometric growth of the otolith and may become more pronounced in older, larger individuals as the differential growth along the otolith axes becomes less uniform with age. Further, laser ablation techniques can examine life history profiles and discern fluctuations over time, proving a preferred application over solution-based analysis.

The impact of a fairytale-like story on the food choices of preschool children - Anoushiravan Zahedi; Stephen Katembu; Sharon Michelle Sind; Undine Sommer; Charles Kimamo; Werner Sommer (Appetite, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Demonstration of the carbon capture with building make-up air unit - Poorandokht Ilani-Kashkouli; Jamieson Brechtl; Keju An; Michelle Kidder; Costas Tsouris; Christopher Janke; Stephen Kowalski; Cheng-Min Yang; M. Muneeshwaran; Meghan Lamm; Katie Copenhaver; Brian Fricke; et al. (Energy and Buildings, 2024)

Seasonal Effects on the Fecal Microbial Composition of Wild Greater Thick-Tailed Galagos (Otolemur crassicaudatus) - Channen Long; Juan Scheun; Michelle Linda Sauther; Frank P. Cuozzo; James Millette; Adrian Stephen Wolferstan Tordiffe (International Journal of Primatology, 2024)
Bacterial communities present in the host digestive tract are important for the breakdown and absorption of nutrients required by the host. Changes in diet and the environment are major factors affecting the composition and diversity of the fecal microbiome. In addition to changes in ambient temperature and rainfall, primates living in seasonal temperate environments also need to adapt to seasonal changes in food resource quantity and quality. However, there is a lack of information about the fecal microbiome in African strepsirrhines relative to other primate taxa. We examined the effects of seasonal dietary and environmental changes on fecal microbial alpha diversity and composition in wild greater thick-tailed galagos ( Otolemur crassicaudatus ) at Lajuma Research Centre, South Africa. We collected fecal samples and assessed food availability and weather in summer and winter across 1 year and used 16S rRNA next-generation sequencing to characterise the fecal microbiome of 49 animals. We found significant increases in rainfall, ambient temperature, and food availability in summer compared with winter. However, we found no significant changes in body mass or in the overall diversity of bacterial species present in fecal samples between the two seasons. We found significant decreases in the abundance of certain bacterial families in winter, suggesting a change in diet. Our findings suggest that greater thick-tailed galagos can find food resources to maintain their body mass throughout the year. Our insights into the seasonal fecal microbiome of greater thick-tailed galagos add to the growing knowledge and understanding of fecal microbiomes in primates and how they help primates cope with changes to their environments.

Genetic parameters for Mycoplasma ovipneumoniae nasal DNA copy number provide progress to promote domestic and bighorn sheep coexistence on public lands - Carrie S. Wilson; J. Bret Taylor; Michelle R. Mousel; Stephen N. White; Lindsay M.W. Piel; Hailey Wilmer; Brenda M. Murdoch (Small Ruminant Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Molecular and morphological support for transferring the tropical African species of Gnidia to Lasiosiphon (Thymelaeaceae: Thymelaeoideae) and a worldwide synopsis of the species - Oluwayemisi D. Olaniyan; J. Stephen Boatwright; Anthony R. Magee; John C. Manning; Michelle van der Bank (Plant Systematics and Evolution, 2024)
Lasiosiphon Fresen. (Thymelaeaceae: Thymelaeoideae) is now understood to be a morphologically diverse genus distributed across southern and tropical Africa, Madagascar, and India. It is diagnosed morphologically by ± involucrate, mostly pedunculate heads of pentamerous or tetramerous flowers, with or without petaloid scales, and a bright yellow, orange, or red corolla. The taxonomic history of Lasiosiphon has been marked by several revisions in its circumscription and status, particularly regarding its relationship with Gnidia L. Our phylogenetic analysis of nuclear (ITS) and plastid ( mat K , rbc L , rps 16 and trn L-F) regions of an expanded sampling of the tropical African species of Gnidia provides compelling supporting evidence for existing morphological evidence to include all the tropical African species of Gnidia in Lasiosiphon . We accordingly provide 31 new combinations in Lasiosiphon for species of Gnidia that currently lack combinations in that genus. We also provide a comprehensive nomenclator of all currently recognized Lasiosiphon species at the regional level encompassing their distribution across different geographic regions globally. This will serve as the framework for future taxonomic revisions in the genus.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Warming reduces trophic diversity in high‐latitude food webs - Michelle C. Jackson; Eoin J. O'Gorman; Bruno Gallo; Sarah F. Harpenslager; Kate Randall; Danielle N. Harris; Hannah Prentice; Mark Trimmer; Ian Sanders; Alex J. Dumbrell; Tom C. Cameron; Katrin Layer‐Dobra; et al. (Global Change Biology, 2024)
The physical effects of climate warming have been well documented, but the biological responses are far less well known, especially at the ecosystem level and at large (intercontinental) scales. Global warming over the next century is generally predicted to reduce food web complexity, but this is rarely tested empirically due to the dearth of studies isolating the effects of temperature on complex natural food webs. To overcome this obstacle, we used ‘natural experiments’ across 14 streams in Iceland and Russia, with natural warming of up to 20°C above the coldest stream in each high‐latitude region, where anthropogenic warming is predicted to be especially rapid. Using biomass‐weighted stable isotope data, we found that community isotopic divergence (a universal, taxon‐free measure of trophic diversity) was consistently lower in warmer streams. We also found a clear shift towards greater assimilation of autochthonous carbon, which was driven by increasing dominance of herbivores but without a concomitant increase in algal stocks. Overall, our results support the prediction that higher temperatures will simplify high‐latitude freshwater ecosystems and provide the first mechanistic glimpses of how warming alters energy transfer through food webs at intercontinental scales.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Research priorities on microplastics in marine and coastal environments: An Australian perspective to advance global action - Nina Wootton; Bronwyn M. Gillanders; Sophie Leterme; Warwick Noble; Scott P. Wilson; Michelle Blewitt; Stephen E. Swearer; Patrick Reis-Santos (Marine Pollution Bulletin, 2024)

Insight into the mechanism of action of ORG27569 at the cannabinoid type one receptor utilising a unified mathematical model - Hayley M. Green; Liang Yang; Xiao Zhu; David B. Finlay; Stephen B. Duffull; Michelle Glass (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Allosteric modulation of CB 1 is therapeutically advantageous compared to orthosteric activation as it potentially offers reduced on-target adverse effects. ORG27569 is an allosteric modulator that increases orthosteric agonist binding to CB 1 but decreases functional signalling. ORG27569 is characterised by a delay in disinhibition of agonist-induced cAMP inhibition (lag); however, the mechanism behind this kinetic lag is yet to be identified. We aimed to utilise a mathematical model to predict data and design in vitro experiments to elucidate mechanisms behind the unique signalling profile of ORG27569. The established kinetic ternary complex model includes the existence of a transitional state of CB 1 bound to ORG27569 and CP55940 and was used to simulate kinetic cAMP data using NONMEM 7.4 and Matlab R2020b. These data were compared with empirical cAMP BRET data in HEK293 cells stably expressing hCB 1 . The pharmacometric model suggested that the kinetic lag in cAMP disinhibition by ORG27569 is caused by signal amplification in the cAMP assay and can be reduced by decreasing receptor number. This was confirmed experimentally, as reducing receptor number through agonist-induced internalisation resulted in a decreased kinetic lag by ORG27569. ORG27569 was found to have a similar interaction with CP55940 and the high efficacy agonist WIN55,212-2, and was suggested to have lower affinity for CB 1 bound by the partial agonist THC compared to CP55940. Allosteric modulators have unique signalling profiles that are often difficult to interrogate exclusively in vitro. We have used a combined mathematical and in vitro approach to prove that ORG27569 causes a delay in disinhibition of agonist-induced cAMP inhibition due to large receptor reserve in this pathway. We also used the pharmacometric model to investigate the common phenomenon of probe dependence, to propose that ORG27569 binds with higher affinity to CB 1 bound by high efficacy orthosteric agonists.

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Novel gas exposure system for the controlled exposure of plants to gaseous hydrogen fluoride - Katherine F. DeMille; Stephen D. Emsbo-Mattingly; Gary Krieger; Michael Howard; Katie B. Webster; Michelle DaCosta (Environmental Monitoring and Assessment, 2023)
Plants can serve as sensitive bioindicators of the presence of contaminant vapors in the atmosphere. This work describes a novel laboratory-based gas exposure system capable of calibrating plants as bioindicators for the detection and delineation of the atmospheric contaminant hydrogen fluoride (HF) as a preparatory step for monitoring release emissions. To evaluate changes in plant phenotype and stress-induced physiological effects attributed to HF alone, the gas exposure chamber must have additional controls to simulate otherwise optimal plant growth conditions including variables such as light intensity, photoperiod, temperature, and irrigation. The exposure system was designed to maintain constant growth conditions during a series of independent experiments that varied between optimal (control) and stressful (HF exposure) conditions. The system was also designed to ensure the safe handling and application of HF. An initial system calibration introduced HF gas into the exposure chamber and monitored HF concentrations by cavity ring-down spectroscopy for a 48-h period. Stable concentrations inside the exposure chamber were observed after approximately 15 h, and losses of HF to the system ranged from 88 to 91%. A model plant species ( Festuca arundinacea ) was then exposed to HF for 48 h. Visual phenotype stress-induced responses aligned with symptoms reported in the literature for fluoride exposure (tip dieback and discoloration along the dieback transition margin). Fluoride concentrations in exposed tissues compared to control tissues confirmed enhanced fluoride uptake due to HF exposure. The system described herein can be applied to other reactive atmospheric pollutants of interest in support of bioindicator research.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

The History and Evolution of PMEL: Purposeful Research that Impacts Environmental Policy - Michelle McClure; Christopher Sabine; Richard Feely; Stephen Hammond; Christian Meinig; Michael McPhaden; Phyllis Stabeno; Eddie Bernard (Oceanography, 2023)
The Pacific Marine Environmental Laboratory (PMEL) conducts global and regional oceanographic research in support of the National Oceanic and Atmospheric Administration’s (NOAA’s) three mission areas: (1) understanding and predicting changes in climate, weather, oceans, and coasts; (2) sharing that knowledge with others; and (3) conserving and managing coastal and marine ecosystems and resources. Since its establishment in 1973, PMEL’s work has ranged from pole to pole and across the global ocean. The lab’s research has examined ocean structure and function in the physical, chemical, and biological realms, and has informed and supported the development of US policy in these areas.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Climate change and Australia’s primary industries: factors hampering an effective and coordinated response - Rebecca Olive Darbyshire; Stephen B. Johnson; Muhuddin Rajin Anwar; Forough Ataollahi; David Burch; Curtis Champion; Melinda A. Coleman; James Lawson; Sarah E. McDonald; Michelle Miller; Jianhua Mo; Mary Timms; et al. (International Journal of Biometeorology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Annotated expression and activity data for murine recombinase alleles and transgenes: the CrePortal resource - Michelle N. Perry; Constance M. Smith; Hiroaki Onda; Martin Ringwald; Stephen A. Murray; Cynthia L. Smith (Mammalian Genome, 2022)
Recombinase alleles and transgenes can be used to facilitate spatio-temporal specificity of gene disruption or transgene expression. However, the versatility of this in vivo recombination system relies on having detailed and accurate characterization of recombinase expression and activity to enable selection of the appropriate allele or transgene. The CrePortal ( http://www.informatics.jax.org/home/recombinase ) leverages the informatics infrastructure of Mouse Genome Informatics to integrate data from the scientific literature, direct data submissions from the scientific community at-large, and from major projects developing new recombinase lines and characterizing recombinase expression and specificity patterns. Searching the CrePortal by recombinase activity or specific recombinase gene driver provides users with a recombinase alleles and transgenes activity tissue summary and matrix comparison of gene expression and recombinase activity with links to generation details, a recombinase activity grid, and associated phenotype annotations. Future improvements will add cell type-based activity annotations. The CrePortal provides a comprehensive presentation of recombinase allele and transgene data to assist researchers in selection of the recombinase allele or transgene based on where and when recombination is desired.

Soft-Sediment Communities of the Northern Indian River Lagoon, FL, United States - Jessica Lunt; Christopher J. Freeman; Dean S. Janiak; Katrina Bayliss; Michelle Stephens; Eve Galimany; Valerie J. Paul (Frontiers in Marine Science, 2021)
Understanding the structure and function of infaunal communities is useful in determining the biodiversity and ecosystem function of shallow estuaries. We conducted a survey of infaunal communities within three separate water basins [Mosquito Lagoon (ML), Indian River (IR), and Banana River (BR)] in the larger Northern Indian River Lagoon, FL, United States to establish a database of infaunal community structure and function. Twenty-seven sites were sampled quarterly from 2014 to 2016. Analysis of all samples determined that basin, season, and sediment composition were the primary drivers of macrobenthic community composition. Diversity was highest in the ML, and lower in spring compared to other seasons. The occurrence of a brown tide ( Aureoumbra lagunensis ) in 2016 allowed a comparison of winter and spring communities before (2015) and during (2016) a bloom event. Community composition and diversity at the BR sites were the most affected by the bloom event with the lowest diversity and abundances during the bloom. Diversity in the IR was also lower during the bloom, while the ML was unaffected by the bloom. Species of all feeding groups were affected by the bloom, with lower abundances found in all groups. In addition, to determine the overall trophic diversity of infaunal communities, we collected infaunal organisms from two of the quarterly sampled sites for isotope analyses. Values of δ 13 C and δ 15 N from infaunal tissue were compared to those of potential food sources at each site. Substantial interspecific variation in isotope values of infaunal organisms within a site suggests the presence of diverse nutritional modes that include suspension and deposit feeding and predation. Together, these data suggest that infaunal communities contribute to benthic pelagic coupling and nutrient cycling within the estuarine communities, but the overall function of these communities may be tightly linked to their species composition.

A new indole alkaloid and other constituents from Monodora minor and Uvaria tanzaniae : their antitrypanosomal and antiplasmodial evaluation - Robert Christopher; Quintino A. Mgani; Stephen S. Nyandoro; Amanda L. Rousseau; Michelle Isaacs; Heinrich C. Hoppe (Natural Product Research, 2021)

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Assessing the State of Coupled Social-Ecological Modeling in Support of Ecosystem Based Fisheries Management in the United States - Stephen Kasperski; Geret S. DePiper; Alan C. Haynie; Suzana Blake; Lisa L. Colburn; Amy Freitag; Michael Jepson; Mandy Karnauskas; Kirsten M. Leong; Douglas Lipton; Michelle Masi; Cameron Speir; et al. (Frontiers in Marine Science, 2021)
There has been a proliferation of coupled social-ecological systems (SES) models created and published in recent years. However, the degree of coupling between natural and social systems varies widely across the different coupled models and is often a function of the disciplinary background of the team conducting the research. This manuscript examines models developed for and used by NOAA Fisheries in support of Ecosystem Based Fisheries Management (EBFM) in the United States. It provides resource managers and interdisciplinary scientists insights on the strengths and weaknesses of the most commonly used SES models: end-to-end models, conceptual models, bioeconomic models, management strategy evaluations (MSEs), fisher behavior models, integrated social vulnerability models, and regional economic impact models. These model types are not unique to the literature, but allow us to differentiate between one-way coupled models – where outputs from one model are inputs into a second model of another discipline with no feedback to the first model, and two-way coupled models – where there are linkages between the natural and social system models. For a model to provide useful strategic or tactical advice, it should only be coupled to the degree necessary to understand the important dynamics/responses of the system and to create management-relevant performance metrics or potential risks from an (in)action. However, one key finding is to not wait to integrate! This paper highlights the importance of “when” the coupling happens, as timing affects the ability to fully address management questions and multi-sectoral usage conflicts that consider the full SES for EBFM or ecosystem based management (EBM) more generally.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

The impact of the indica rice SSIIa allele on the apparent high amylose starch from rice grain with downregulated japonica SBEIIb - Jixun Luo; Vito M. Butardo; Qiang Yang; Christine Konik-Rose; Michelle L. Colgrave; Anthony Millar; Stephen A. Jobling; Zhongyi Li (Theoretical and Applied Genetics, 2020)

Analysis of viruses present in urine from patients with interstitial cystitis - Maria Teresa Sáenz Robles; Paul G. Cantalupo; Alexis M. Duray; Melissa Freeland; Michelle Murkowski; Adrie van Bokhoven; Alisa J. Stephens-Shields; James M. Pipas; Michael J. Imperiale (Virus Genes, 2020)

Rapid Assessment of Wetland Condition Reflects Amphibian Community Composition - Kari Dupler; Michelle Guidugli-Cook; David R. Brown; Stephen C. Richter (Wetlands, 2020)

Comparing Rates of Linage Diversification with Rates of Size and Shape Evolution in Catarrhine Crania - Evan A. Simons; Stephen R. Frost; Katerina Harvati; Kieran McNulty; Michelle Singleton (Evolutionary Biology, 2020)

Geopolitics and Marine Conservation: Synergies and Conflicts - Peter Charles Mackelworth; Yael Teff Seker; Tomás Vega Fernández; Márcia Marques; Fátima Lopes Alves; Giovanni D’Anna; Darren A. Fa; David Goldborough; Zacharoula Kyriazi; Cristina Pita; Michelle E. Portman; Bob Rumes; et al. (Frontiers in Marine Science, 2019)

Applying Unoccupied Aircraft Systems to Study Human Behavior in Marine Science and Conservation Programs - Michelle B. Nowlin; Stephen E. Roady; Everette Newton; David W. Johnston (Frontiers in Marine Science, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Kenneth Neil Mertens; Nicolas Van Nieuwenhove; Pieter R. Gurdebeke; Hilal Aydin; Kara Bogus; Manuel Bringué; Barrie Dale; Stijn De Schepper; Anne de Vernal; Marianne Ellegaard; Arjen Grothe; Haifeng Gu; et al. (Palynology, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Chronosequence predictions are robust in a Neotropical secondary forest, but plots miss the mark - Justin M. Becknell; Stephen Porder; Steven Hancock; Robin L. Chazdon; Michelle A. Hofton; James B. Blair; James R. Kellner (Global Change Biology, 2018)
Tropical secondary forests (TSF) are a global carbon sink of 1.6 Pg C/year. However, TSF carbon uptake is estimated using chronosequence studies that assume differently aged forests can be used to predict change in aboveground biomass density (AGBD) over time. We tested this assumption using two airborne lidar datasets separated by 11.5 years over a Neotropical landscape. Using data from 1998, we predicted canopy height and AGBD within 1.1 and 10.3% of observations in 2009, with higher accuracy for forest height than AGBD and for older TSFs in comparison to younger ones. This result indicates that the space‐for‐time assumption is robust at the landscape‐scale. However, since lidar measurements of secondary tropical forest are rare, we used the 1998 lidar dataset to test how well plot‐based studies quantify the mean TSF height and biomass in a landscape. We found that the sample area required to produce estimates of height or AGBD close to the landscape mean is larger than the typical area sampled in secondary forest chronosequence studies. For example, estimating AGBD within 10% of the landscape mean requires more than thirty 0.1 ha plots per age class, and more total area for larger plots. We conclude that under‐sampling in ground‐based studies may introduce error into estimations of the TSF carbon sink, and that this error can be reduced by more extensive use of lidar measurements.

Multiple hypotheses explain variation in extra‐pair paternity at different levels in a single bird family - Lyanne Brouwer; Martijn van de Pol; Nataly Hidalgo Aranzamendi; Glen Bain; Daniel T. Baldassarre; Lesley C. Brooker; Michael G. Brooker; Diane Colombelli‐Négrel; Erik Enbody; Kurt Gielow; Michelle L. Hall; Allison E. Johnson; et al. (Molecular Ecology, 2017)
Extra‐pair paternity ( EPP ), where offspring are sired by a male other than the social male, varies enormously both within and among species. Trying to explain this variation has proved difficult because the majority of the interspecific variation is phylogenetically based. Ideally, variation in EPP should be investigated in closely related species, but clades with sufficient variation are rare. We present a comprehensive multifactorial test to explain variation in EPP among individuals in 20 populations of nine species over 89 years from a single bird family (Maluridae). Females had higher EPP in the presence of more helpers, more neighbours or if paired incestuously. Furthermore, higher EPP occurred in years with many incestuous pairs, populations with many helpers and species with high male density or in which males provide less care. Altogether, these variables accounted for 48% of the total and 89% of the interspecific and interpopulation variation in EPP . These findings indicate why consistent patterns in EPP have been so challenging to detect and suggest that a single predictor is unlikely to account for the enormous variation in EPP across levels of analysis. Nevertheless, it also shows that existing hypotheses can explain the variation in EPP well and that the density of males in particular is a good predictor to explain variation in EPP among species when a large part of the confounding effect of phylogeny is excluded.

Field-based assessment of wetland condition, wetland extent, and the National Wetlands Inventory in Kentucky, USA - Michelle Guidugli-Cook; Stephen C. Richter; Barbara J. Scott; David R. Brown (Wetlands Ecology and Management, 2017)

Rib Geometry Explains Variation in Dynamic Structural Response: Potential Implications for Frontal Impact Fracture Risk - Michelle M. Murach; Yun-Seok Kang; Samuel D. Goldman; Michelle A. Schafman; Stephen H. Schlecht; Kevin Moorhouse; John H. Bolte; Amanda M. Agnew (Annals of Biomedical Engineering, 2017)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Estimation of on-road NO2 concentrations, NO2/NOX ratios, and related roadway gradients from near-road monitoring data - Jennifer Richmond-Bryant; R. Chris Owen; Stephen Graham; Michelle Snyder; Stephen McDow; Michelle Oakes; Sue Kimbrough (Air Quality, Atmosphere & Health, 2017)

Thermal constraints on foraging of tropical canopy ants - Michelle Elise Spicer; Alyssa Y. Stark; Benjamin J. Adams; Riley Kneale; Michael Kaspari; Stephen P. Yanoviak (Oecologia, 2017)

Hybrid plants preserve unique genetic variation in the St Helena endemic trees Commidendrum rotundifolium DC Roxb. and C. spurium (G.Forst.) DC - Alan Gray; Annika Perry; Stephen Cavers; Antonia Eastwood; Michelle Biermann; Andrew Darlow; Vanessa Thomas; Phil Lambdon (Conservation Genetics, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Exploration of the effects of classroom humidity levels on teachers’ respiratory symptoms - Kim A. Angelon-Gaetz; David B. Richardson; Stephen W. Marshall; Michelle L. Hernandez (International Archives of Occupational and Environmental Health, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Methodology of Motor Evoked Potentials in a Rabbit Model - Stephen D. Waterford; Michelle Rastegar; Erin Goodwin; Paul A. Lapchak; Viviana Juan; Farnaz Haji; René Bombien; Ali Khoynezhad (Translational Stroke Research, 2015)

The different effects of starch synthase IIa mutations or variation on endosperm amylose content of barley, wheat and rice are determined by the distribution of starch synthase I and starch branching enzyme IIb between the starch granule and amyloplast stroma - Jixun Luo; Regina Ahmed; Behjat Kosar-Hashemi; Oscar Larroque; Vito M. Butardo; Greg J. Tanner; Michelle L. Colgrave; Narayana M. Upadhyaya; Ian J. Tetlow; Michael J. Emes; Anthony Millar; Stephen A. Jobling; et al. (Theoretical and Applied Genetics, 2015)

A novel allele of Alx4 results in reduced Fgf10 expression and failure of eyelid fusion in mice - Michelle Curtain; Caleb S. Heffner; Dennis M. Maddox; Polyxeni Gudis; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2015)

Switchgrass Establishment Influenced by Cover Crop, Tillage Systems, and Weed Control - Amir Sadeghpour; Masoud Hashemi; Michelle DaCosta; Emad Jahanzad; Stephen J. Herbert (BioEnergy Research, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

A physiological analysis of color vision in batoid elasmobranchs - Christine N. Bedore; Ellis R. Loew; Tamara M. Frank; Robert E. Hueter; D. Michelle McComb; Stephen M. Kajiura (Journal of Comparative Physiology A, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Transatlantic migration by post-breeding puffins: a strategy to exploit a temporarily abundant food resource? - Mark J. Jessopp; Michelle Cronin; Thomas K. Doyle; Mark Wilson; Abigail McQuatters-Gollop; Stephen Newton; Richard A. Phillips (Marine Biology, 2013)

Spatial and temporal analysis of killer whale ( Orcinus orca ) strandings in the North Pacific Ocean and the benefits of a coordinated stranding response protocol - Michelle M. Barbieri; Stephen Raverty; M. Bradley Hanson; Stephanie Venn‐Watson; John K. B. Ford; Joseph K. Gaydos (Marine Mammal Science, 2013)
Killer whales ( Orcinus orca ) are widely distributed throughout the world's oceans, yet little has been documented about their stranding patterns. Knowledge of stranding patterns improves our ability to examine and sample carcasses and provides a foundation for understanding killer whale natural history, diet, reproduction, anthropogenic stressors, emerging diseases, and patterns of unusual mortality. We compiled published and unpublished killer whale stranding data to describe stranding patterns in the North Pacific Ocean. Between 1925 and 2011, 371 stranded killer whales were reported in Japan (20.4%), Russia (3.5%), Alaska (32.0%), British Columbia (27.4%), Washington (4.0%), Oregon (2.7%), California (5.1%), Mexico (3.8%), and Hawaii (0.8%). Strandings occurred at all times of year, but regionally specific seasonal differences were observed. Mortality and annual census data from Northern and Southern Resident populations were extrapolated to estimate that across the North Pacific, an average of 48 killer whales die annually. However, over the last two decades, an average of only 10 killer whale carcasses were recovered annually in this ocean, making each event a rare opportunity for study. Publication of a standardized killer whale necropsy protocol and dedicated funding facilitated the number of complete postmortem necropsies performed on stranded killer whales from 1.6% to 32.2% annually.

The influence of landscape on gene flow in the eastern massasauga rattlesnake ( Sistrurus c. catenatus ): insight from computer simulations - Michelle F. DiLeo; Jeremy D. Rouse; José A. Dávila; Stephen C. Lougheed (Molecular Ecology, 2013)
Understanding how gene flow shapes contemporary population structure requires the explicit consideration of landscape composition and configuration. New landscape genetic approaches allow us to link such heterogeneity to gene flow within and among populations. However, the attribution of cause is difficult when landscape features are spatially correlated, or when genetic patterns reflect past events. We use spatial Bayesian clustering and landscape resistance analysis to identify the landscape features that influence gene flow across two regional populations of the eastern massasauga rattlesnake, S istrurus c. catenatus . Based on spatially explicit simulations, we inferred how habitat distribution modulates gene flow and attempted to disentangle the effects of spatially confounded landscape features. We found genetic clustering across one regional landscape but not the other, and also local differences in the effect of landscape on gene flow. Beyond the effects of isolation‐by‐distance, water bodies appear to underlie genetic differentiation among individuals in one regional population. Significant effects of roads were additionally detected locally, but these effects are possibly confounded with the signal of water bodies. In contrast, we found no signal of isolation‐by‐distance or landscape effects on genetic structure in the other regional population. Our simulations imply that these local differences have arisen as a result of differences in population density or tendencies for juvenile rather than adult dispersal. Importantly, our simulations also demonstrate that the ability to detect the consequences of contemporary anthropogenic landscape features (e.g. roads) on gene flow may be compromised when long‐standing natural features (e.g. water bodies) co‐exist on the landscape.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

A multi-model ensemble of downscaled spatial climate change scenarios for the Dommel catchment, Western Europe - Michelle T. H. van Vliet; Stephen Blenkinsop; Aidan Burton; Colin Harpham; Hans Peter Broers; Hayley J. Fowler (Climatic Change, 2012)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Clonidine blocks stress-induced craving in cocaine users - Michelle L. Jobes; Udi E. Ghitza; David H. Epstein; Karran A. Phillips; Stephen J. Heishman; Kenzie L. Preston (Psychopharmacology, 2011)

Scale-dependent selection of greenness by African elephants in the Kruger-private reserve transboundary region, South Africa - Jason P. Marshal; Azhar Rajah; Francesca Parrini; Michelle Henley; Stephen R. Henley; Barend F. N. Erasmus (European Journal of Wildlife Research, 2011)

Human papillomavirus is not associated with colorectal cancer in a large international study - Michele C. Gornick; Xavier Castellsague; Gloria Sanchez; Thomas J. Giordano; Michelle Vinco; Joel K. Greenson; Gabriel Capella; Leon Raskin; Gad Rennert; Stephen B. Gruber; Victor Moreno (Cancer Causes & Control, 2010)

Introduced ungulate herbivore alters soil processes after fire - Michelle L. Stritar; Jennifer A. Schweitzer; Stephen C. Hart; Joseph K. Bailey (Biological Invasions, 2010)

Lithium therapy for human immunodeficiency virus type 1–associated neurocognitive impairment - Giovanni Schifitto; Jianhui Zhong; David Gill; Derick R Peterson; Michelle D Gaugh; Tong Zhu; Madalina Tivarus; Kim Cruttenden; Sanjay B Maggirwar; Howard E Gendelman; Stephen Dewhurst; Harris A Gelbard (Journal of NeuroVirology, 2009)

Unique glycine‐activated riboswitch linked to glycine–serine auxotrophy in SAR11 - H. James Tripp; Michael S. Schwalbach; Michelle M. Meyer; Joshua B. Kitner; Ronald R. Breaker; Stephen J. Giovannoni (Environmental Microbiology, 2009)
Summary The genome sequence of the marine bacterium ‘ Candidatus Pelagibacter ubique’ and subsequent analyses have shown that while it has a genome as small as many obligate parasites, it nonetheless possesses a metabolic repertoire that allows it to grow as one of the most successful free‐living cells in the ocean. An early report based on metabolic reconstruction indicated that SAR11 cells are prototrophs for all amino acids. However, here we report experimental evidence that ‘ Cand. P. ubique’ is effectively auxotrophic for glycine and serine. With glucose and acetate added to seawater to supply organic carbon, the addition of 125 nM to 1.5 μM glycine to growth medium containing all other nutrients in excess resulted in a linear increase in maximum cell density from 1.14 × 10 6 cells ml −1 to 8.16 × 10 6 cells ml −1 ( R 2 = 0.992). Serine was capable of substituting for glycine at 1.5 μM. ‘ Cand. P. ubique’ contains a glycine‐activated riboswitch preceding malate synthase, an unusual genomic context that is conserved in the SAR11 group. Malate synthase plays a critical role in central metabolism by enabling TCA intermediates to be regenerated through the glyoxylate cycle. In vitro analysis of this riboswitch indicated that it responds solely to glycine but not close structural analogues, such as glycine betaine, malate, glyoxylate, glycolate, alanine, serine or threonine. We conclude that ‘ Cand. P. ubique’ is therefore a glycine–serine auxotroph that appears to use intracellular glycine level to regulate its use of carbon for biosynthesis and energy. Comparative genomics and metagenomics indicate that these conclusions may hold throughout much of the SAR11 clade.

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

Predation by rainbow trout (Oncorhynchus mykiss) on a Western Australian icon: Marron (Cherax cainii) - Michelle Y. Tay; Alan J. Lymbery; Stephen J. Beatty; David L. Morgan (New Zealand Journal of Marine and Freshwater Research, 2007)
Considerable numbers of rainbow trout (Oncorhynchus mykiss) are captively produced then stocked into many wild aquatic systems in Western Australia despite a lack of understanding of their impact on the highly endemic native fish and freshwater crayfish of the region. The diet of an introduced, yet self‐sustaining population of O. mykiss was examined at Churchman Brook Reservoir in the Canning River Catchment, Western Australia, between September and November 2004. The large endemic freshwater crayfish marron (Cherax cainii) , which supports an iconic recreational fishery in Western Australia, comprised 61% by volume of all O. mykiss stomachs examined. The contribution made by C. cainii to the assimilated biomass of O. mykiss was confirmed by stable isotope analyses, which revealed that it dominated the assimilated diet of larger O. mykiss . The substantial contribution of C. cainii to the diet of wild O. mykiss suggests that, at least in habitat limited water bodies, it is likely to have a considerable predatory impact on C. cainii populations and may compromise some elements of this iconic recreational fishery.

Evaluation of Fumigants, EPTC Herbicide, and Paenibacillus macerans in the Production of Loblolly Pine Seedlings - Michelle M. Cram; Scott A. Enebak; Stephen W. Fraedrich; Lew D. Dwinell; Stanley J. Zarnoch (Forest Science, 2007)
Chloropicrin fumigation, Eptam 7-E (EPTC) herbicide, and Paenibacillus macerans seed treatments were evaluated as alternatives to fumigation with methyl bromide/chloropicrin for loblolly pine (Pinus taeda L.) seedling production at three nurseries in the southern United States. A treatment of metam sodium/chloropicrin was also evaluated at one nursery. Seedling density was unaffected by fumigation and EPTC treatments at all nurseries. Seedling diameter and shoot weight were greater in some chloropicrin treatments during the first year at the southern Georgia nursery. The only measurable disease losses were caused by a nematode, Longidorus americanus, at the southern Georgia nursery. Soil-borne population densities of Pythium and Fusarium spp. did not significantly differ between methyl bromide and the other fumigant treatments at any nursery. Chloropicrin controlled nutsedge (Cyperus spp.) in the loamy sand soils at the southern Georgia nursery, but there were no differences between the control and the fumigant treatments at the Alabama nursery, and nutsedge was rarely found at the northern Georgia nursery. The herbicide EPTC had no effect on nutsedge when compared to the controls at all nurseries and the effects of the bacterial seed treatment were inconsistent among the nurseries. Chloropicrin and metam sodium/chloropicrin can be effective alternatives to methyl bromide for reducing soil-borne fungi and nematodes, but the effectiveness of chloropicrin for nutsedge control may be affected by soil type.

Common variants in the TCF7L2 gene and predisposition to type 2 diabetes in UK European Whites, Indian Asians and Afro-Caribbean men and women - Steve E. Humphries; David Gable; Jackie A. Cooper; Helen Ireland; Jeffrey W. Stephens; Steven J. Hurel; Ka Wah Li; Jutta Palmen; Michelle A. Miller; Francesco P. Cappuccio; Robert Elkeles; Ian Godsland; et al. (Journal of Molecular Medicine, 2006)

Zebra Mussel Antifouling Activity of the Marine Natural Product Aaptamine and Analogs - Jeffrey A. Diers; John J. Bowling; Stephen O. Duke; Subagus Wahyuono; Michelle Kelly; Mark T. Hamann (Marine Biotechnology, 2006)

Mitochondrial DNA phylogeography of western lowland gorillas ( Gorilla gorilla gorilla ) - Stephen L. Clifford; Nicola M. Anthony; Mireille Bawe‐Johnson; Kate A. Abernethy; Caroline E. G. Tutin; Lee J. T. White; Magdelena Bermejo; Michelle L. Goldsmith; Kelley McFarland; Kathryn J. Jeffery; Michael W. Bruford; E. Jean Wickings (Molecular Ecology, 2004)
The geographical distribution of genetic variation within western lowland gorillas ( Gorilla gorilla gorilla ) was examined to clarify the population genetic structure and recent evolutionary history of this group. DNA was amplified from shed hair collected from sites across the range of the three traditionally recognized gorilla subspecies: western lowland ( G. g. gorilla ), eastern lowland ( G. g. graueri ) and mountain ( G. g. beringei ) gorillas. Nucleotide sequence variation was examined in the first hypervariable domain of the mitochondrial control region and was much higher in western lowland gorillas than in either of the other two subspecies. In addition to recapitulating the major evolutionary split between eastern and western lowland gorillas, phylogenetic analysis indicates a phylogeographical division within western lowland gorillas, one haplogroup comprising gorilla populations from eastern Nigeria through to southeast Cameroon and a second comprising all other western lowland gorillas. Within this second haplogroup, haplotypes appear to be partitioned geographically into three subgroups: (i) Equatorial Guinea, (ii) Central African Republic, and (iii) Gabon and adjacent Congo. There is also evidence of limited haplotype admixture in northeastern Gabon and southeast Cameroon. The phylogeographical patterns are broadly consistent with those predicted by current Pleistocene refuge hypotheses for the region and suggest that historical events have played an important role in shaping the population structure of this subspecies.

Decreased Neurotropism of nef Long Terminal Repeat ( nef /LTR)-Deleted Simian Immunodeficiency Virus - Katherine A Thompson; Stephen J Kent; Michelle E Gahan; Damian FJ Purcell; Catriona A McLean; Scott Preiss; C Jane Dale; Steven L Wesselingh (Journal of NeuroVirology, 2003)

The discriminative stimulus properties of self-administered ethanol are mediated by GABA A and NMDA receptors in rats - Clyde W. Hodge; Amy A. Cox; Alison M. Bratt; Rosana Camarini; Kimberly Iller; Stephen P. Kelley; Kristin K. Mehmert; Michelle A. Nannini; M. Foster Olive (Psychopharmacology, 2001)

Assessing Phytoestrogen Exposure in Epidemiologic Studies: Development of a Database (United States) - Pamela L. Horn-Ross; Stephen Barnes; Marion Lee; Lori Coward; J. Elizabeth Mandel; Jocelyn Koo; Esther M. John; Michelle Smith (Cancer Causes & Control, 2000)

The incidence of gastric carcinoma in Asian migrants to the United States and their descendants - Aruna Kamineni; Michelle A. Williams; Stephen M. Schwartz; Linda S. Cook; Noel S. Weiss (Cancer Causes & Control, 1999)